Interest of Youth of the Batak Karo Protestant Church (GBKP) Cikarang in Using Regional Language Communication - Rivaldo, Brema (Advances In Social Humanities Research, 2024)
This study examines the interest of the youth of the Batak Karo Protestant Church (GBKP) Cikarang in the use of regional language communication. There is a phenomenon of the lack of interest of GBKP youth in using regional languages ??in communicating. Regional languages ??play an important role in describing cultural identity. Along with the shifting developments in the era of globalization, the interest in using regional languages ??will gradually be replaced by contemporary languages ??that change the way of communication between fellow GBKP Cikarang youth. The purpose of this study was to determine the interest of GBKP youth in using Karo language in the era of globalization. The research method used Qualitative research. The location of the research was at the GBKP Cikarang Church, West Java. Data collection techniques used interviews, observation, and documentation. This study used the Ethnolinguistic Vitality Theory to determine the factors influencing the use of regional languages. The results of the study showed that: (1) the interest of GBKP youth in using Karo language in Cikarang experienced a real decline, this finding also revealed that interest was not completely lost, because GBKP youth were more pressured by an irregular or changing environment. (2) factors that influence the use of Karo language in communicating the role of family, environment and the era of globalization and the demands of the times. The use of Karo language among GBKP youth in Cikarang, West Java, has experienced a significant decline. Although there are variations in the understanding and use of Karo language depending on family background, place of residence and social interaction, in general the interest of GBKP youth in using their mother tongue has declined.